Mixing and chemical ozone loss during and after the Antarctic polar vortex major warming in September 2002 - Konopka, Paul; Grooß, J.-U.; Hoppel, K. W.; Steinhorst, H.-M.; Müller, R. (Journal of the Atmospheric Sciences, 2005)
The 3D version of the Chemical Lagrangian Model of the Stratosphere (CLAMS) is used to study the transport of CH4 and 03 in the Antarctic stratosphere between I September and 30 November 2002, that is, over the time period when unprecedented major stratospheric warming in late September split the polar vortex into two parts. The isentropic and cross-isentropic velocities in CLAMS are derived from ECMWF winds and heating/cooling rates calculated with a radiation module. The irreversible part of transport, that is, mixing, is driven by the local horizontal strain and vertical shear rates with mixing parameters deduced from in situ observations.The CH4 distribution after the vortex split shows a completely different behavior above and below 600 K. Above this potential temperature level, until the beginning of November, a significant part of vortex air is transported into the midlatitudes up to 40 degrees S. The lifetime of the vortex remnants formed after the vortex split decreases with the altitude with values of about 3 and 6 weeks at 900 and 700 K, respectively.Despite this enormous dynamical disturbance of the vortex, the intact part between 400 and 600 K that "survived" the major warming was strongly isolated from the extravortex air until the end of November. According to CLAMS simulations, the air masses within this part of the vortex did not experience any significant dilution with the midlatitude air.By transporting ozone in CLAMS as a passive tracer, the chemical ozone loss was estimated from the difference between the observed [Polar Ozone and Aerosol Measurement III (POAM 111) and Halogen Occultation Experiment (HALOE)] and simulated ozone profiles. Starting from I September, up to 2.0 ppmv O-3 around 480 K and about 70 Dobson units between 450 and 550 K were destroyed until the vortex was split. After the major warming, no additional ozone loss can be derived, but in the intact vortex part between 450 and 550 K, the accumulated ozone loss was "frozen in" until the end of November.